2014
DOI: 10.1124/dmd.114.058099
|View full text |Cite
|
Sign up to set email alerts
|

Deciding on Success Criteria for Predictability of Pharmacokinetic Parameters from In Vitro Studies: An Analysis Based on In Vivo Observations

Abstract: Prediction accuracy of pharmacokinetic parameters is often assessed using prediction fold error, i.e., being within 2-, 3-, or n-fold of observed values. However, published studies disagree on which fold error represents an accurate prediction. In addition, "observed data" from only one clinical study are often used as the gold standard for in vitro to in vivo extrapolation (IVIVE) studies, despite data being subject to significant interstudy variability and subjective selection from various available reports.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 18 publications
(16 reference statements)
8
121
0
Order By: Relevance
“…The PBPK modeling approach could predict clearance for all nine drugs in the studies from infants to adolescents (1 month to 18 years old). The twofold range of the prediction accuracy is a commonly used standard in pediatric PK modeling, and in vitro‐in vivo extrapolation prediction . Although twofold boundaries are wide for drugs with PK parameters that have low variability and have been accurately characterized with large sample size, such boundaries are considered reasonable when the observed data are obtained from studies with small sample size .…”
Section: Discussionmentioning
confidence: 99%
“…The PBPK modeling approach could predict clearance for all nine drugs in the studies from infants to adolescents (1 month to 18 years old). The twofold range of the prediction accuracy is a commonly used standard in pediatric PK modeling, and in vitro‐in vivo extrapolation prediction . Although twofold boundaries are wide for drugs with PK parameters that have low variability and have been accurately characterized with large sample size, such boundaries are considered reasonable when the observed data are obtained from studies with small sample size .…”
Section: Discussionmentioning
confidence: 99%
“…The exposure was defined as maximum plasma concentration (C max ) or AUC. Several success criteria (1.25‐fold or 2‐fold range) have been used in the literature . Here, a 1.5‐fold range was chosen on the basis of the intrinsic PK variability of efavirenz, as well as the moderate‐to‐mild extent of efavirenz perpetrated DDIs …”
Section: Methodsmentioning
confidence: 99%
“…More careful reporting of the simulated and observed study populations would also be critically important when model performance is assessed. As has been highlighted in the literature (Abduljalil et al, 2014), PBPK simulations are often compared to clinical studies with small study populations, and the true inter-and intraindividual variability of the observed PK parameters of the compound of interest are not known. This can lead to a situation in which one clinical study does not accurately predict the PK parameters observed in another study with the same compound (Abduljalil et al, 2014).…”
Section: Data Sets Used In Model Verification Included: (A) Single Domentioning
confidence: 99%